KONTRIBUSI NILAI-NILAI ISLAM TERHADAP PENGUATAN KARAKTER SISWA DALAM PEMBELAJARAN KONTEMPORER - Indah Aprilia Sari Harahap; Febri Ajia; Sri Aldani Sibuea (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to explore the role of Islamic values in student character development. Islamic values such as faith, morals, and sharia can serve as a moral and ethical foundation for students in facing various challenges and problems in everyday life. This study uses literature study and critical analysis methods to understand how Islamic values can be integrated into student character education. The results show that Islamic values can play an important role in shaping the character of students who have noble morals, have an awareness of their responsibilities as servants of God and citizens, and become individuals who contribute positively to society. This research is expected to contribute to the development of character education in schools, especially in the context of Islamic education. This study confirms that Islamic values function as a moral foundation and an effective normative framework in shaping balanced student character (lawazun), encompassing spiritual, intellectual, and social aspects. Schools that optimize this role have successfully shown a decrease in cases of moral violations and an increase in positive student attitudes.